2016
DOI: 10.17664/ksgee.2016.12.4.027
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of a Cascade Heat Pump with Two-stage Water Heating Process

Abstract: It is estimated that only heating and cooling take about one third of the total energy consumption worldwide. However, the conventional heating and cooling systems have low efficiencies. Also, boilers and electric heaters that are mostly used to generate both domestic and industrial hot water are inefficient and high energy consumers. For this reason, cascade heat pumps which are known to be very energy efficient and have less environmental impact are being promoted to replace conventional heating, cooling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Recent studies have been conducted to improve the performance of the two-stage heat pump system. Jang et al 37 demonstrated that a two-stage heat pump system increased the heating capacity of the system and increased the system COP by 16.5% when the system operated in the DHW mode. Yrjölä et al 38 also proposed a two-stage GSHP system for space heating and DHW.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have been conducted to improve the performance of the two-stage heat pump system. Jang et al 37 demonstrated that a two-stage heat pump system increased the heating capacity of the system and increased the system COP by 16.5% when the system operated in the DHW mode. Yrjölä et al 38 also proposed a two-stage GSHP system for space heating and DHW.…”
Section: Introductionmentioning
confidence: 99%